Make miracles in forty days : turning what you have into what you want - Beattie, Melody (Simon & Schuster, 2010)
We've all had situations in our lives that seem beyond our control or that have no clear remedy. In this concise, inspirational guide, bestselling self-help guru Melody Beattie shows us that we have the ability to make a miracle for almost any circumstance we're facing. She offers a distillation of what she knows about gratitude, surrender, and connecting with our essential power. She challenges us to be more present each day and details a six-week action plan, the Miracle Exercise, to jump-start transformation in our lives.--From publisher description.